2007
DOI: 10.2349/biij.3.2.e18
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation in general radiography

Abstract: Radiography using film has been an established method for imaging the internal organs of the body for over 100 years. Surveys carried out during the 1980s identified a wide range in patient doses showing that there was scope for dosage reduction in many hospitals. This paper discusses factors that need to be considered in optimising the performance of radiographic equipment. The most important factor is choice of the screen/film combination, and the preparation of automatic exposure control devices to suit its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 22 publications
1
36
0
8
Order By: Relevance
“…The ideal set of parameters to describe IQ should measure the effectiveness with which an image can be used for its intended purpose. 24 The general scoring framework set out in this study follows the European guidelines although the IQ criteria have been set on the specific diagnostic requirements of paediatric extremity imaging, as defined by the clinicians at ELCH. As discussed previously, the primary issue with the IQ of the radiographs using the default parameters is the difficulty in differentiating between the cortexes of the tibia and surrounding soft tissue.…”
Section: Contrast-to-noise Ratio Measurementsmentioning
confidence: 99%
“…The ideal set of parameters to describe IQ should measure the effectiveness with which an image can be used for its intended purpose. 24 The general scoring framework set out in this study follows the European guidelines although the IQ criteria have been set on the specific diagnostic requirements of paediatric extremity imaging, as defined by the clinicians at ELCH. As discussed previously, the primary issue with the IQ of the radiographs using the default parameters is the difficulty in differentiating between the cortexes of the tibia and surrounding soft tissue.…”
Section: Contrast-to-noise Ratio Measurementsmentioning
confidence: 99%
“…One simple but effective method of radiation dose reduction is the replacement of the traditionally performed anteroposterior (AP) projection with the posteroanterior (PA) projection. Martin (2007), in a recent review of the literature, found evidence that PA projections are often favoured over an AP projection on occasions where radiosensitive organs are lying closest to the anterior surface of the body (2). Despite this it is still common practice for the majority of UK departments to perform lumbar spine examinations using the AP position.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of image quality are essential for optimization of the radiography processes in any clinical settings [5]. Guidelines have been set up by the European Commission (EC) for assessing the basic aspects of quality for clinical radiographic images dependent on techniques and imaging performance [3]. Generally, high image quality provides maximum information, improve the chance for correct diagnosis and ultimately contribute to quality patient care.…”
Section: Introductionmentioning
confidence: 99%
“…It is more important that the observer interpret the image appropriately than whether the appearance of the image is pleasing to the eye. The ideal set of parameters to describe image quality should measure the effectiveness with which an image can be used for its intended purpose [3].…”
Section: Introductionmentioning
confidence: 99%